algebra

posted by .

how do i figure: (-12a^2b^6)^3 over (9a^3b^9)^3

  • algebra -

    (-12a^2b^6)^3 / (9a^3b^9)^3
    = ( (-12a^2b^6)/(9a^3b^9) )^3
    = ( (-4/3)(1/a)(1/b^3) )^3
    = (-64/27)(1/a^3)(1/b^9)
    = -64/( 27a^3b^9 )

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    12a-18b/-6 simplify
  2. algebra 2

    If f(3a-1) = 12a-7, what is f(x)?
  3. mathematics

    12a^2b over 4 times 4a+8b over 20a^2b^3
  4. Algebra

    (9a^3b^4-12a^2b^5+6ab^7)/(6a^2b^3)
  5. Algebra II

    Factor: 12a^2-17a-5
  6. algebra

    -12a+3(2a+1)=-6a
  7. Algebra 1 (Reiny)

    12a - 11 = 9a - 1?
  8. Algebra 1

    Divide. Simplify your answer. 1. 3a^4b/2a^2c^3 รท 12a^2c/8c^4 A: ?
  9. algebra

    simplify -2a^+6ab^-12a^b/-24ab the b -12a^b the b is to the third power 2a^b/24ab + 6ab^/24ab -12a^b to the third/24ab 12a+4ab +2ab^ 2ab^+4ab +12a
  10. algebra

    simplify 2a^2 + 6ab^2-12a^2b^3 divided by 24ab -2a^2/-24ab + 6ab^2/24ab--12a^2b^3/24ab= -12ab^2 +12a +4b

More Similar Questions